Socialization of Student Injury Management during Sports Activities for Teacher at Eria Junior High School - Epi Supriyani Siregar; Budi Alamsyah Siregar; Dewi Suma (Journal of Community Research and Service, 2023)
The purpose of this community service is to understand the Handling of Student Injuries during the time of the Sports Teachers at Eria High School. The service was carried out at Eria Junior High School. Data collection techniques used include observation techniques, interviews, and documentation. Data analysis in research took place simultaneously with the data collection process. It was achieved using three phases of the model, namely data redaction, data synthesis, and data verification. Based on data analysis from the initial survey conducted at Eria High School, it can be concluded that there were still a lot of anxiety around Olympic fencing training. There was training for understanding that was more basic and easy to implement based on the results of discussions on handling injuries to students. It can be done based on personal experience. For this reason, this service was carried out for training. The results of the discussion were  presented by socialization and instructions with the aim of assisting teachers and students. By providing scientific knowledge in the field of handling sports injuries using the RICE method,  it is expected to make it easier for teachers and students in Eria Junior High School.